1996
DOI: 10.1104/pp.111.4.1251
|View full text |Cite
|
Sign up to set email alerts
|

Two Genes Encode Highly Similar Chloroplastic NADP-Malic Enzymes in Flaveria (Implications for the Evolution of C4 Photosynthesis)

Abstract: To gain an understanding of the molecular events underlying the evolution of C, photosynthesis, we have undertaken a detailed study of the NADP-malic enzyme gene family in C, and C, species of Haveria. Three genomic clones from the C, species Haveria bidentis were characterized and found to encode two highly similar chloroplastic forms of NADP-malic enzyme, termed ME1 and ME2. Genomic Southern blotting with gene-specific probes showed that both Me7 and Me2 are found in Haveria trinervia (C,) and fiaveria pring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 17 publications
(26 reference statements)
4
49
1
Order By: Relevance
“…CA1 and CA3 precursor polypeptides were imported into isolated pea chloroplasts, and concomitant with import was processing of the CA1 and CA3 precursors to lower molecular mass polypeptides, which were protected from externally added protease. Work with other C 4 photosynthetic enzymes from C 3 and C 4 Flaveria species has shown that alterations in gene expression patterns occurred during the evolution of the C 4 forms of the enzymes, which have resulted in their increased levels of expression and celland organ-specific expression patterns (Marshall et al, 1996;Drincovich et al, 1998;Rosche et al, 1998;Lai et al, 2002;Gowik et al, 2004). Similar modifications are anticipated to have occurred during the evolution of the gene encoding the C 4 form of b-CA.…”
Section: F Pringlei Contains Two Chloroplastic B-casmentioning
confidence: 73%
See 3 more Smart Citations
“…CA1 and CA3 precursor polypeptides were imported into isolated pea chloroplasts, and concomitant with import was processing of the CA1 and CA3 precursors to lower molecular mass polypeptides, which were protected from externally added protease. Work with other C 4 photosynthetic enzymes from C 3 and C 4 Flaveria species has shown that alterations in gene expression patterns occurred during the evolution of the C 4 forms of the enzymes, which have resulted in their increased levels of expression and celland organ-specific expression patterns (Marshall et al, 1996;Drincovich et al, 1998;Rosche et al, 1998;Lai et al, 2002;Gowik et al, 2004). Similar modifications are anticipated to have occurred during the evolution of the gene encoding the C 4 form of b-CA.…”
Section: F Pringlei Contains Two Chloroplastic B-casmentioning
confidence: 73%
“…Genomic DNA was isolated from leaf tissue according to the method of Marshall et al (1996), and 10-mg aliquots were digested to completion in separate reactions with EcoRI and XbaI. Genomic DNA fragments were separated by electrophoresis on a 0.8% (w/v) agarose gel and transferred to Hybond N + membranes (GE Healthcare Life Sciences) using alkaline capillary blotting (Sambrook et al, 1989).…”
Section: Genomic Southern-blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A similar analysis identified two genes encoding chloroplast-localized ME isoforms in Flaveria (Marshall et al, 1996). One gene, Me1, encodes the C 4 form in the C 4 species.…”
Section: Discussionmentioning
confidence: 82%